Legal Protection Of Pawn Debtors For Damage And Loss Of Collateral Objects In Private Pawn Businesses - Sembiring, Ferdiansah; Siregar, Taufik; Lubis, Aldi Subhan (Program Pascasarjana UIN Sumatera Utara, 2025)
This study aims to analyze legal protection for pawn debtors concerning damage and loss of collateral in private pawn businesses. The growing phenomenon of private pawning practices without formal legality has led to legal uncertainty and increased risks to the rights of debtors. The research method employed is normative legal research with a literature review approach, utilizing data sources such as the Indonesian Civil Code (KUHPerdata), Law Number 8 of 1999 concerning Consumer Protection, Financial Services Authority Regulation (POJK) Number 31/POJK.05/2016 concerning Pawnshop Businesses, and Islamic legal instruments related to pawning (rahn). The results indicate that legal protection for debtors in private pawn businesses remains suboptimal. Although POJK Number 31/POJK.05/2016 provides adequate protection for licensed pawnshops, the regulation does not extend to individual private pawn practices. Consequently, debtors face difficulties in asserting their rights when collateral is damaged or lost. From the perspective of Islamic law, the principles of amanah (trustworthiness) and 'adl (justice) require the pawn recipient (murtahin) to safeguard and return the pledged item in good condition and to provide compensation in the event of negligence. This study recommends the need for regulatory reform to broaden the scope of legal protection to encompass all forms of pawn businesses, including home-based pawn operations. Integrating Islamic legal values, such as justice, trustworthiness, and consumer protection, into national regulations is essential to strengthen the legal standing of debtors and to create fairer, safer pawn transactions oriented toward public welfare. Thus, strengthening debtor protection not only reinforces the microfinance system but also supports the principle of social justice in Indonesia.